URGENSI UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL SEBAGAI PERLINDUNGAN HUKUM TERHADAP LAKI-LAKI DEWASA KORBAN KEKERASAN SEKSUAL - Agisna Viet Maulida (2022)
The crime of sexual violence can happen to anyone including adult men who can become victims, it is not uncommon for views from the community regarding an unbalanced assessment of a community group, namely to men who are often not considered a serious matter by the community. society. The regulation of criminal acts of sexual violence in the Indonesian Criminal Code which is still considered lacking in protection of certain parties or groups is the author's idea or idea to suggest that there is a need to improve the provisions on the regulation of criminal acts of sexual violence in Indonesia. The problem in this study is how the urgency of regulating sexual violence crimes is expected to be a solution for the community, especially victims of the crime of sexual violence. On April 12, 2022, the House of Representatives of the Republic of Indonesia passed Law Number 12 of 2022 concerning criminal acts of sexual violence. The law is expected to protect the dignity of victims, but as a state of law it is necessary to have derivative regulations that formulate standard operating procedures for the implementation of criminal acts of sexual violence.